The Lisbon Treaty law, politics, and treaty reform - Craig, P. P. (Paul P.) (Oxford : Oxford University Press, 2010)
This title offers an overview of the principal reforms to the European Union brought about by the Lisbon Treaty. It gives an account of the extended Treaty reform process, analyses the main legal and governance changes effected by the Treaty, and examines these against the background political forces that shaped the new provisions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union -- Constitution; European Union -- Reform; Treaty on European Union, -- (1992). -- 2007 Dec. 13.; European Union countries -- Foreign relations -- Treaties; Law